Engineering economics - Panneerselvam, R (Prentice-Hall of India Private Limited, 2012)
Designed as a text book for undergraduate students in various engineering disciplines - mechanical, civil and industrial engineering - and for postgraduate students in industrial engineering and water resource management, this comprehensive and well-organized book shows how complex economic decisions can be made from a number of given alternatives. It provides the managers not only a sound basis but also a clear-cut approach to decision making. These decisions will ultimately result in minimizing costs and/or maximizing benefits to their organizations. What is more, the book adequately illustrates these approaches with numerical problems and Indian cases. After giving an overview of the subject, the text discusses, in a simple and easy-to-read style, such topics as interest formulas and their applications, methods like present worth method of comparison, future worth method, annual equivalent method, rate of return method, and evaluation of public alternatives. Besides, it deals with depreciation, inflation adjusted decisions, and inventory control. Finally, the book analyzes other important areas, for instance, make or buy decision, project management, value analysis/value engineering, and linear programming. A distinguishing feature of the book is that it has an Appendix on interest tables for a wide range of interest rates (0.25% - 50%) and for a period ranging from one year to 100 years. This book, which is profusely illustrated with worked-out examples and diagrams, should prove extremely useful not only as a text book but also as a reference for those offering courses in such management areas as project management, production management and financial management.